Review: Assessing Strategic Litigation Impact on Human Rights - Gebara Fallah, Diego (Revista Direito e Práxis, 2019)
DOI: 10.1590/2179-8966/2019/39380 Assessing Strategic Litigation Impact on Human Rights Duffy Helen. Strategic Human Rights Litigation: Understanding and Maximising Impact. Oxford: Hart Publishing, 2018. Diego Gebara Fallah Universidade de Maastricht, Maastricht, Holanda. ORCID: https://orcid.org/0000-0001-8090-6424.